Transcriptome Analysis of the Effect of Acute Ammonia Stress on Pseudobagrus ussuriensis Liver Tissue - Shun Shi; Xiaohui Sun; Chunnuan Zhang; Chenran Lv; Yajuan Liu; Juan Du; Qian Qi (Fishes)
Excess ammonia can damage the growth and development of fish. Pseudobagrus ussuriensis is a scaleless fish with important economic value that is more sensitive to ammonia stress. In this study, P. ussuriensis was explored using different ammonia concentrations [control (0 mg/L), CL; low stress (10 mg/L), T1L; and high stress (50 mg/L), T2L] for 48 h. Compared to the control group, the liver cells in the T1L group showed slight damage, while the T2L group was severely damaged, with the cells being loosely arranged, with nuclei lysis and cell vacuolization. The activities of superoxide dismutase, catalase, and glutathione in the T1L and T2L groups were significantly lower than those in the CL group (p < 0.05), and the malondialdehyde reached the maximum at 48 h. Furthermore, 9301 differentially expressed genes (DEGs) (4583 upregulated and 4718 downregulated) were detected by transcriptome sequencing. Most DEGs were highly enriched in cellular processes (GO:0009987) and cell parts (GO:0044464). Especially, the phosphatidylinositol 3-kinase/protein kinase B (PI3K-Akt) signaling pathway had the maximum quantity of DEGs in all the three groups. In-depth analysis revealed the stress caused multiple substitutions of SNP sites in pik3ca and kras, blocking the PI3K/Akt signaling pathway to prevent cancer cell proliferation and spread, accelerating the apoptosis of damaged cells. These results suggest that ammonia stress induces liver damage in P. ussuriensis, causing genetic mutations and cellular carcinogenesis, thereby accelerating cell apoptosis.